Anemia en niños y su efecto del tratamiento en un establecimiento de salud de Lima: Anemia in children and its effect of treatment in primary healthcare of Lima - Cardenas-Venancio, Karolay Nicole (2021)
Treatment of anemia with ferrous sulfate in children under three years of age is effective. Likewise, there is a direct relationship between the hemoglobin level and the number of months of treatment.